2013
DOI: 10.3390/ijms140611145
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tumor Markers, NSE, CA125 and SCC, in Operable NSCLC Patients

Abstract: The aim of this study was to investigate the prognostic value of tumor markers in operable non-small cell lung cancer (NSCLC) patients. A total of 481 NSCLC patients were enrolled in the present study. High levels of neuron-specific enolase (NSE), carbohydrate antigen 125 (CA125) and squamous cell carcinoma antigen (SCC) were detected in 306 (63.6%), 89 (18.5%) and 125 (26.0%) patients, respectively. Seventy-eight of 481 patients died of disease progression, and the median disease-free survival (DFS) and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 33 publications
4
67
0
1
Order By: Relevance
“…Nowadays, a series of biomarkers have been recommended to diagnose and manage those patients with lung cancer, including CEA, NSE, CYFRA21-1 and SCCA (15,16). Since cancer biomarker discovery has started extensively with the progress of proteomic technology, many protein molecules have been indicated as potential cancer biomarkers (17).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, a series of biomarkers have been recommended to diagnose and manage those patients with lung cancer, including CEA, NSE, CYFRA21-1 and SCCA (15,16). Since cancer biomarker discovery has started extensively with the progress of proteomic technology, many protein molecules have been indicated as potential cancer biomarkers (17).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical laboratory echnicians found that combined tumor markers has relatively higher sensitivity in daily work. Researchers found that combined detection had great value in the diagnosis, analysis of effect, recurrence detection and prognosis of cancer (Duffy et al, 2013;Li et al, 2013;Sisik et al, 2013;Wang et al, 2013;Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the univariate Cox regression analysis, we assigned the SIG12 score of the 12 genes as follows: SIG12 score = (0.324 × expression value of ADM) + (−0.379 × expression value of CYSLTR1) + (0.353 × expression value of DDIT4) + (−0.326 × expression value of DOCK8) + (0.29 × expression value of ENO2) + (−0.28 × expression value of FCER1A) + (−0.286 × expression value of IL17A) + (−0.328 × expression value of IZUMO4) + (−0.273 × expression value of MMP25) + (−0.362 × expression value of P2RY14) + (0.292 × expression value of RBP4) + (−0.299 × expression value of ZNF252P‐AS1). The known or putative functions and clinical relevance are described in Table .…”
Section: Resultsmentioning
confidence: 99%